ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG KAKI LIMA KERUPUK IKAN DI KENJERAN SURABAYA - solikha, warda; penagsang, parikesit (JEB17 : Jurnal Ekonomi dan Bisnis, 2021)
The income earned by street vendors is determined by various factors, including the capital, working hours, and length of business. This study aims to analyze the effect of the variables of capital, working hours, and length of business on the income of street vendors (PKL) in the Coastal Area of Kenjeran Beach, Surabaya. This study uses primary data through direct interviews with 50 respondents at street vendors in the Coastal Area of Kenjeran Surabaya, with a list of prepared questions. To achieve the goal, this study uses the Multiple Linear Regression analysis method. This study uses calculations through SPSS 22.0. The results of this study indicate that the variables of capital, working hours, and length of business have a positive effect on the income of street vendors in the Kenjeran Coastal Coastal Area of Surabaya